Laboratory Investigation of Behavioural Changes in Tensile Strength of Bituminous Concrete Mixes Subjected to Differential Loading Temperature - Aleruchi Igwe, Enwuso; Nyebuchi, Daniel Azeruibe (IJRDO - Journal of Mechanical And Civil Engineering, 2017)
This paper presents a laboratory investigation of the behaviour of bituminous concrete mixtures when subjected to differential loadings in temperature with respect to tensile strength. The study became necessary because previous works have revealed that bitumen which is the binding agent in bituminous concrete can easily flow or flush under increased temperature causing separation from aggregates. For the present study, laboratory specimens of bituminous concretes were prepared in accordance with specified standards and two indirect tensile testing methods (split cylinder and double punch tests) were used to evaluate the behavioural changes in tensile strength that occurred. The laboratory procedure involved testing the specimens under increasing temperature of loading between 20°C - 60°C with incremental loadings of 10°C. The study was carried out for three categories of traffic – Light, Medium and Heavy traffic categories respectively. The results obtained revealed that increase in mix temperature of asphalt/bituminous concretes from 20°C - 60°C adversely affected the tensile strength behaviour of the concrete under external traffic loading. Furthermore, results of tensile strength from the double punch test were better than those from split cylinder test for all categories of traffic under varying temperature between 20°C - 60°C.